Inclusive J/[psi] production at forward and backward rapidity in p-Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; et al. (Journal of high energy physics, 2018)
Inclusive J/ψ production is studied in p-Pb interactions at a centre-of-mass energy per nucleon-nucleon collision sNN−−−√=8.16sNN=8.16 \sqrt{s_{NN}}=8.16 TeV, using the ALICE detector at the CERN LHC. The J/ψ meson is reconstructed, via its decay to a muon pair, in the centre-of-mass rapidity intervals 2.03 < ycms < 3.53 and −4.46 < ycms < −2.96, where positive and negative ycms refer to the p-going and Pb-going direction, respectively. The transverse momentum coverage is pT < 20 GeV/c. In this paper, ycms- and pT-differential cross sections for inclusive J/ψ production are presented, and the corresponding nuclear modification factors RpPb are shown. Forward results show a suppression of the J/ψ yield with respect to pp collisions, concentrated in the region pT ≲ 5 GeV/c. At backward rapidity no significant suppression is observed. The results are compared to previous measurements by ALICE in p-Pb collisions at sNN−−−√=5.02sNN=5.02 \sqrt{s_{NN}}=5.02 TeV and to theoretical calculations. Finally, the ratios RFB between forward- and backward-ycms RpPb values are shown and discussed. Open image in new window